2016
DOI: 10.1007/s40430-016-0590-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental efficiency analysis of sugarcane bagasse boilers based on the first law of thermodynamics

Abstract: List of symbolsA Area (m 2 ) C Carbon content (%) c Specific heat (kJ/kg K) h Enthalpy (kJ/kg) H Heat transfer coefficient (kW/m 2 °C) HV Heat value HHV Higher heating value (kJ/kg) L Energy loss (%) LHV Lower heating value (kJ/kg) m Proportion of material flow per kilogramme of fuel (kg/kg) m Mass flow rate (kg/s) Q Available heat (kJ/kg) Q Heat flow (kW) T Temperature (°C) U Uncertainty x Mass fraction (kg/kg) Greek letters λ Water vaporisation heat (kJ/kg) η First law efficiency Subscripts ash Ashes ah Drum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…It will also reduce the per unit cost of electricity linked with biomass-based power plants and will attract the investors to invest in the biomass-based power plants. [10,17,20,44]…”
Section: Energy Forecasting For Rice Husk Power Generation In Pakistanmentioning
confidence: 99%
See 1 more Smart Citation
“…It will also reduce the per unit cost of electricity linked with biomass-based power plants and will attract the investors to invest in the biomass-based power plants. [10,17,20,44]…”
Section: Energy Forecasting For Rice Husk Power Generation In Pakistanmentioning
confidence: 99%
“…Edgar et al analysed sugarcane bagasse boiler using the first law of thermodynamics and based upon the results, they concluded that moisture content in the biomass is the major cause of low efficiency. Other losses they described were due to hydrogen conversion into water and losses through stack [17]. Modern technologies like organic Rankine cycle (ORC) are better for burning of biomass.…”
Section: Introductionmentioning
confidence: 99%
“…These are the five most common losses present in regular steam generators. Cortes-Rodríguez et al [5] indicated that use of fuel HHV (high heating value) revealed important energy losses related to fuel moisture (usually relevant when biomass is used as fuel). Furthermore, they highlighted that the term related to fuel energy input, which is difficult to obtain when some solid fuels are used, should be calculated as in Eq.…”
Section: Thermodynamic Evaluation Of Steam Generators 21 Energy Analmentioning
confidence: 99%
“…Equation 1, also referred to as "the indirect method" or "stack loss method", is usually preferable in detriment of the direct efficiency equation ("direct method"), η = (ṁ steam .�h)/(ṁ fuel .LHV) [5,20]. Propagation of measurement errors is usually reduced using the indirect method since the magnitude of measured losses is smaller than the magnitude of useful product.…”
Section: Thermodynamic Evaluation Of Steam Generators 21 Energy Analmentioning
confidence: 99%
See 1 more Smart Citation